PENGEMBANGAN KOMIK MATEMATIKA BERBASIS KONSTRUKTIVISME PADA TOPIK SEGIEMPAT DAN SEGITIGA KELAS VII SMP/ MTs - Rizka Zulhiaswan (Departemen Matematika, 2021)
Every learning process requires teaching materials. Teaching materials have a role in achieving learning objectives. However, the teaching materials used in schools have not opened up diverse thinking insights from all students and motivate students to read them, so teaching materials in the form of comics based on constructivism have been developed on the material of rectangles and triangles. This type of research is Ploom which aims to produce valid and practical comics teaching materials. This research consists of a preliminary research, development or prototyping phase, and an assessment phase. The research instrument consisted of a questionnaire obbservation sheet validation sheet, interview list and practicality questionnaire. The results of this study indicate that the quality of the teaching materials developed is very valid from the aspect of the material according to the curriculum, the aspect of the appearance is good and attractive, has all the components of teaching materials and aspects of language that are good and correct. This comics teaching material is very practical because it is easy to use, understandable, and develops students' thinking insight. Keywords— teaching materials, comics, constructivism, ploom, quadrilaterals and triangles